2013
DOI: 10.1111/jam.12063
|View full text |Cite
|
Sign up to set email alerts
|

New screening methods for probiotics with adhesion properties to sialic acid and sulphate residues in human colonic mucin using the Biacore assay

Abstract: Aims: To determine the relationship between adhesive ability of probiotics and acidic residues in human colonic mucin, we developed a new screening method using Biacore to evaluate adherence of bacteria before and after sialic acid or sulphate residues were blocked or removed from mucin. Methods and Results: Ten strains of lactobacilli and three strains of bifidobacteria isolated from human faeces were evaluated for their adhesive properties to soluble human colonic mucin (sHCM) using the Biacore binding assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Interestingly, adhesion of B. animalis subsp. animalis MCC-1489 was significantly increased after sulfatase treatment, suggesting that the binding sites may be exposed after sulfatase treatment, as described by Huang et al, 14) who showed similar interactions in the adhesion of Lactobacillus ME-522 and B. bifidum MCC-1092 to mucin. However, additional studies are needed to characterize the binding properties of B. animalis subsp.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Interestingly, adhesion of B. animalis subsp. animalis MCC-1489 was significantly increased after sulfatase treatment, suggesting that the binding sites may be exposed after sulfatase treatment, as described by Huang et al, 14) who showed similar interactions in the adhesion of Lactobacillus ME-522 and B. bifidum MCC-1092 to mucin. However, additional studies are needed to characterize the binding properties of B. animalis subsp.…”
Section: Discussionsupporting
confidence: 70%
“…12) Thus, for probiotics, including bifidobacteria, adhesion to acidic mucins is thought to be an advantage for survival during transit and colonization in the intestinal tract. [13][14][15] The interactions between Bifidobacterium strains and carbohydrate moieties of glycoconjugates, including glycolipids and mucins, have been described previously; for example, Bifidobacterium pseudolongum ATCC 25526 and Bifidobacterium adolescentis VTT E-001561 specifically adhere to α-1,4-linked glucose sugars, 16) while Bifidobacterium bifidum EB102 and Bifidobacterium longum SBT2928 bind to gangliotetraosylceramide. 17,18) A recent study showed that B. bifidum MCC-1092 binds to both sialic acid and sulfated carbohydrates of human colonic mucins because adhesion of the bacterium to mucins was reduced by treatment with sialidase and sulfatase and blocked by barium chloride.…”
mentioning
confidence: 81%
“…Probiotic lactobacilli are further selected for their ability to adhere to mucus and epithelial cells, as these characteristics are essential for their ability to colonize the gut's mucosal and epithelial layer and enhance their competitiveness against pathogens (Huang et al . ; Valeriano et al . ).…”
Section: Probiotic Adhesion Is An Important Trait For Colonization Anmentioning
confidence: 99%
“…Autochthonous lactobacilli are frequently selected as potential probiotics because of their natural ability to withstand the harsh physiological conditions caused by stomach acid, bile salts and pancreatic enzymes during their passage through the GIT (Walter 2008). Probiotic lactobacilli are further selected for their ability to adhere to mucus and epithelial cells, as these characteristics are essential for their ability to colonize the gut's mucosal and epithelial layer and enhance their competitiveness against pathogens (Huang et al 2013;Valeriano et al 2014). This competitive profile is most likely present in autochthonous lactobacilli, which are used as biomarkers of health and are important components of the gut microflora of pigs.…”
Section: Probiotic Adhesion Is An Important Trait For Colonization Anmentioning
confidence: 99%
“…Methodologies to screen for bacterial adhesion to mucins have previously employed thin layer chromatography overlay [26], enzyme-linked immunosorbent assay [15], micro-titre plate assays [8,25,27], surface plasmon resonance [16,28,29,30,31], fluorescence spectroscopy [20], mucin microarrays [32], flow cytometry [33], and cell-based assays [26,34,35,36]. However, due to the complexity and diversity of mucin glycosylation, these methods typically provide qualitative binding data indicating only presence or absence of interaction.…”
Section: Introductionmentioning
confidence: 99%